Formation of hydrogen sulfide in isolated basins at the Karelian White Sea coast ... - Losyuk, Galina; Kokryatskaya, Nataliya; Krasnova, Elena (EARSeL eProceedings, 2015)
The results of a study of the formation of hydrogen sulfide in isolated basins, which are at different stages of isolation in Kandalaksha Bay of the White Sea, are presented. It has been demonstrated that hydrogen sulfide has developed in higher degrees in a basin mostly isolated from the sea. This basin shows pronounced features of meromixis. Accumulation of hydrogen sulfide in lakes, where the salt water periodically flows in from the sea, is connected with the development of seasonal stratification and anaerobic conditions in the bottom waters. The concentration of hydrogen sulfide increases from the surface to the near-bottom layer, where the highest concentrations of H2S were determined in all basins. ...